Effect of Mg on Mechanical Properties of Al-Mg Alloys - Caydas, Ulas; Hascalik, Ahmet (Carl Hanser Verlag, 2010)
In this study, the effect of Mg content on the mechanical properties of Al-Mg alloys was investigated. For this, five different alloys were produced by conventional casting method. Tension, Charpy and fatigue tests were carried out and hardness measurements were conducted on the alloys. Fatigue tests were performed using a rotational bending fatigue test machine and the fatigue strength has been analysed by drawing S-N curves and critically observing fatigue fracture surfaces of the tested samples. The microstructure of the alloys and fracture surfaces were examined by optical and scanning electron microscopy (SEM). The experimental results indicate that mechanical properties are significantly affected by the addition of Mg and the fatigue strength of samples increased due to solid solution strengthening with increasing Mg content in chosen conditions.
Auswirkungen von Mg auf die mechanischen Eigenschaften von Al-Mg-Leglerungen
Keywords: Precipitation; Deformation; Fracture